2013
DOI: 10.1093/cvr/cvt029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte ryanodine receptor degradation by chaperone-mediated autophagy

Abstract: These findings are consistent with a model in which oxidative damage of the RyR2 targets it for turnover by presenilins and CMA, which could lead to removal of damaged or leaky RyR2 channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…The activation of these proteases was evaluated by determining the cleavage of pro-caspase 3 to active caspase-3 and of α-spectrin, an important target of activated calpains [34]. As shown in the Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of these proteases was evaluated by determining the cleavage of pro-caspase 3 to active caspase-3 and of α-spectrin, an important target of activated calpains [34]. As shown in the Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of LAMP-2, fusion of autophagosomes with lysosomes is blocked leading to accumulation of long-lived proteins, ultimately resulting in myopathy. Recent studies by Pedrozo et al (2013) demonstrated that the ryanodine receptor type 2 (RyR2), the main cardiac sarcoplasmic reticulum calcium-release channel required for cardiomyocyte excitation-contraction and often associated with myocardial remodeling after ischemia/reperfusion (I/R) and cardiac failure, is degraded by CMA. Furthermore, the authors demonstrated that CMA-mediated degradation of RyR2 induced by oxidative stress depends on presenilins (Pedrozo et al, 2013).…”
Section: Ubiquitin Autophagy and The Heartmentioning
confidence: 99%
“…Interestingly we recently discovered that RYR2 (ryanodine receptor 2 [cardiac]) sequence harbors six KFERQ motifs, and is degraded via chaperone-mediated autophagy. 35 As RYR2 plays a key role in cardiomyocyte excitation-contraction and its dysfunction can contribute to cardiac failure, this observation may have pathophysiological relevance.…”
Section: Autophagymentioning
confidence: 99%